2009
DOI: 10.5303/jkas.2009.42.3.055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Source Position on the Dh-Type Ii Cme Properties

Abstract: The properties of SOHO/LASCO CMEs are subjected to projection effects. Their dependence on the source position is important to be studied. Our main aim is to study the dependence of CME properties on helio-longitude and latitude using the CMEs associated with type IIs observed by Wind/WAVES spacecraft (Deca-hecta metric type IIs -DH type IIs). These CMEs were identified as a separate population of geo-effective CMEs. We considered the CMEs associated with the Wind/WAVE type IIs observed during the period Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…In order to see the dependency of CME properties such as width, speed and acceleration based on longitude, we have grouped the events into three categories ( The limb events have speeds ∼1.4 times greater than the speed of disk events. So, the DH CMEs speed near the disk center is less which is similar to the results reported by many authors (Gopalswamy et al 2001b;Burkepile et al 2004;Michalek et al 2005;Vrsnak et al 2007;Shanmugaraju et al 2009). The CMEs associated with DH type II bursts are more energetic than the metric type II-associated CMEs (Lara et al 2003).The main reason for the longitudinal dependence should be the projection effect.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In order to see the dependency of CME properties such as width, speed and acceleration based on longitude, we have grouped the events into three categories ( The limb events have speeds ∼1.4 times greater than the speed of disk events. So, the DH CMEs speed near the disk center is less which is similar to the results reported by many authors (Gopalswamy et al 2001b;Burkepile et al 2004;Michalek et al 2005;Vrsnak et al 2007;Shanmugaraju et al 2009). The CMEs associated with DH type II bursts are more energetic than the metric type II-associated CMEs (Lara et al 2003).The main reason for the longitudinal dependence should be the projection effect.…”
Section: Discussionsupporting
confidence: 93%
“…The arrows in each plot indicate the mean speed of the distribution. The mean and median speed increases from disk to limb Shanmugaraju et al (2009). reported that the CMEs have more speeds at higher longitudes near the limb than the CMEs observed at lower longitudes near disk centre.…”
mentioning
confidence: 92%
“…1). Here after many authors (Burkepile et al 2004;Michalek et al 2005;Yeh et al 2005;Wen et al 2007;Shanmugaraju et al 2009) pointed out that the projection effect is more important to study the properties of CMEs. The limb events have the minimal projection effect.…”
mentioning
confidence: 96%